How institutional nature and available resources determine the performance of technology transfer offices - Cartaxo, Rui M. (2017)
This paper assesses the performance of GAPIs and OTICs, two different types of university technology transfer offices that have been active in Portuguese higher education institutions, since 2000 and 2006, respectively. Data originating from a survey of these offices were analysed through both cluster analysis and the estimation of a Partial Least Squares-Structural Equation Modelling (PLS-SEM) model. Results show that the institutional nature of each of the surveyed organisations implies different behaviours and outputs. Furthermore, it is shown that the resources and activities of the surveyed offices determine their performance concurrently with regard to technology transfer, licencing contracts and technology-based spin-offs. The results of this study may be particularly relevant for countries that are in the process of developing their university technology transfer activities, as they can help to shape policies in relation to TTOs’ funding and resource allocation during the earlier stages of these activities.